2018
DOI: 10.1016/j.neubiorev.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and systematic review of the literature characterizing auditory mismatch negativity in individuals with autism

Abstract: A number of past studies have used mismatch negativity (MMN) to identify auditory processing deficits in individuals with autism spectrum disorder (ASD). Our meta-analysis compared MMN responses for individuals with ASD and typically developing controls (TD). We analyzed 67 experiments across 22 publications that employed passive, auditory-based MMN paradigms with ASD and TD participants. Most studies lacked design characteristics that would lead to an accurate description of the MMN. Variability between exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
91
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 95 publications
13
91
2
1
Order By: Relevance
“…The undisturbed functioning of the primary auditory cortex in children with ASD is well in line with numerous electrophysiological evidence on their typical, or even enhanced processing of frequency/pitch of pure tones [69][70][71] for review) that mainly relies upon A1 neural circuitry. On the other hand, the SF abnormalities suggestive of abnormal functioning of the 'pitch processing center' in our participants with ASD, generally agree with the conclusion derived from the comprehensive meta-analysis of mismatchnegativity (MMN) studies in autism [71]. The results of this meta-analysis point to a weak neural encoding of spectrally and/or temporally complex non-speech stimuli in the prepubertal children with ASD.…”
Section: Assr In Nt Children and Children With Asdsupporting
confidence: 70%
See 1 more Smart Citation
“…The undisturbed functioning of the primary auditory cortex in children with ASD is well in line with numerous electrophysiological evidence on their typical, or even enhanced processing of frequency/pitch of pure tones [69][70][71] for review) that mainly relies upon A1 neural circuitry. On the other hand, the SF abnormalities suggestive of abnormal functioning of the 'pitch processing center' in our participants with ASD, generally agree with the conclusion derived from the comprehensive meta-analysis of mismatchnegativity (MMN) studies in autism [71]. The results of this meta-analysis point to a weak neural encoding of spectrally and/or temporally complex non-speech stimuli in the prepubertal children with ASD.…”
Section: Assr In Nt Children and Children With Asdsupporting
confidence: 70%
“…Poor quality of MEG recording in children with ASD (see e.g. [71] for discussion) is unlikely to explain the group differences. Indeed, the ASSR phase consistency did not differ between the ASD and NT groups ( Figure 4), pointing to comparable SNR.…”
Section: Assr In Nt Children and Children With Asdmentioning
confidence: 99%
“…According to the results of functional characterization, the maMTG.R was highly associated with hearing and language, which are two vital components of auditory processing. Although many researchers identified auditory processing deficits in adults with ASD and hypothesized that there is a common disruption in the neural network associated with auditory processing in ASD [Bomba & Pang, 2004;Mamashli et al, 2017;Marco, Hinkley, Hill, & Nagarajan, 2011;Schwartz, Shinn-Cunningham, & Tager-Flusberg, 2018], the main brain regions involved in the network are still an open question. Our findings provide evidence that the disruptions of the maMTG.R might be associated with auditory processing deficits in adults with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of literature on other auditory mismatch negativity paradigms in individuals with autism that reports conflicting results. Two recent systematic review and meta-analyses of auditory mismatch negativity studies identified an overall trend toward less pronounced MMN responses to various types of deviant auditory stimuli in individuals with ASD as compared to controls (Chen, Hsieh, Lin, Chan, & Cheng, 2020;Schwartz, Shinn-Cunningham, & Tager-Flusberg, 2018). Yet, these same reviews also described significant variability across studies in the strength and direction of this effect (Chen et al, 2020;Schwartz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent systematic review and meta-analyses of auditory mismatch negativity studies identified an overall trend toward less pronounced MMN responses to various types of deviant auditory stimuli in individuals with ASD as compared to controls (Chen, Hsieh, Lin, Chan, & Cheng, 2020;Schwartz, Shinn-Cunningham, & Tager-Flusberg, 2018). Yet, these same reviews also described significant variability across studies in the strength and direction of this effect (Chen et al, 2020;Schwartz et al, 2018). An advantage of MMN paradigms is that no explicit behavioral response by the participant to the stimuli is required, thus allowing for the inclusion of individuals with a range of ages and cognitive and verbal abilities.…”
Section: Introductionmentioning
confidence: 99%